2020
DOI: 10.1097/md.0000000000020838
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors for congenital hypothyroidism

Abstract: Congenital hypothyroidism (CH) is one of the most common neonatal endocrine diseases. This retrospective cohort study aimed to identify the potential perinatal risk factors for CH and to differentiate between transient and permanent CH (TCH and PCH, respectively) as well as determine their prevalence in a southeastern Chinese population. This study was based on an 18-year surveillance of a neonatal CH screening program in a large tertiary hospital. A retrospective review of the maternal and neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
2
16
0
5
Order By: Relevance
“…By considering the reported group differences, we could design more studies for better understand- ing of different subgroups of CH. As mentioned previously, though there were studies regarding CH-related risk factors (6,34,36,44,47,49,56,59,63) there was no comprehensive review in this field. Moreover, for some important risk factors such as seasonality or gender differences, the results of studies were not in agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By considering the reported group differences, we could design more studies for better understand- ing of different subgroups of CH. As mentioned previously, though there were studies regarding CH-related risk factors (6,34,36,44,47,49,56,59,63) there was no comprehensive review in this field. Moreover, for some important risk factors such as seasonality or gender differences, the results of studies were not in agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reported risk factors, including environmental pollutants (25,58), dietary component of mothers during prenatal period (41,64), neonatal jaundice (47), maternal anemia (48), intrauterine growth retardation (6), lower weight gain during pregnancy (60), urbanization (62), parental occupation and education (35,47), gestational diabetes (6,46,59), and smoking (14,47,60) have limited evidence. It seems that more studies for investigating the association of the mentioned risk factors with CH are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The last study in Fars province (2007) reported 53.6 % permanent CH cases [ 29 ]. Worldwide, 66.44 % of CH cases in the state of Alabama (USA) [ 25 ], 70.6 % in the state of Oregon (USA)[ 26 ], 75 % in the state of Michigan (USA)[ 22 ], 62 % in France [ 31 ], and finally, 46.6 % of CH cases in China were permanent; while the rest were transient [ 32 ]. In our study, 66.04 % had confirmed permanent CH, while only 33.96 % had transient CH.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of parental consanguinity and familial history of thyroid disorders on transient and permanent CH is controversial. While studies by Rabbiosi et al, Dorreh et al, and Saba et al, found first-degree familial thyroid disorders more prevalent in permanent CH patients [ 24 , 34 , 35 ], Zhou et al, found them to be more prevalent in transient CH [ 32 ]. In our study, we did not find any statistical differences in the prevalence of familial thyroid disorders between the two groups, although it should be noted that both were higher than the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation